Non-Sentinel Lymph Nodes Status in Patients with Breast Cancer Operated at Omdurman Teaching Hospital (Global Journal of Medical Research, 2014)
Background: Sentinel lymph node (SLN) biopsy has been emerged as safe and accurate procedure for axillary staging in breast cancer and to direct the need for further axillary treatment in patients with early breast cancer. Objectives: To assess the status of axillaries lymph nodes in patients of breast cancer to determine further management of the axilla and to assess status of non sentinel lymph nodes cases of negative SLN. Patients and methods: It is prospective interventional study done in Omdurman Teaching Hospital, department of General Surgery from 27/6/2012 to 30/8/2013 in patients underwent modified radical mastectomy plus level I and II axillaries clearance by injecting methylene blue dye and identifying sentinel lymph node in patients diagnosed with breast cancer. Results: Total number of 39 female patients under went modified radical mastectomy and level 1 and II axillaries clearances, In 22 patients 56.4% the retrieved sentinel axillary lymph node proved histopathologically to contain malignant cells. In eight patients 20.5% the sentinel lymph node were negative for malignancy and in 09 (23.1%) the SLN was either not found or reactive, Non-sentinel lymph node (NSLN) was found to be positive for malignancy in 11 (28.2%) of the cases. In 23 (59.0%) it was negative and in 05 (12.8%) it was not found. Out of 22 patients with positive SLN, half of them 11 patients were concomitantly had a positive NSLNs and the other half had a negative NSLN. In the eight patients with negative SLN for malignancy, all of them 08 (100%) had their NSLNs as well were negative for malignancy. These relations were found statistically to be highly significant (P value 0.000) none of the patients in study diagnosis as positive NSLN in negative SLN base. Conclusion: Highly occurrence of positive NSLN in patient diagnosis by T3 and T4 in the study, a number of patients diagnosis by positive NSLN in positive SLN was 32, 4 %, none of the patients in study diagnosis by positive NSLN in n
Keywords: breast cancer; sentinel lymph node; sentinel lymph node biopsy; non-sentinel lymph node biopsy